Veterinary laser surgery : - Berger, Noel (Blackwell Pub., 2006)
Surgical and therapeutic use of lasers began in human medicine in the early 1960s. Technology and equipment advanced rapidly. Over the last ten years veterinarians have been exploring the many potential advantages that various lasers provide their patients. Because laser light energy can be applied directly to target tissue or administered to distant lesions at a remote site through fiberoptic components, laser surgery has become an invaluable and growing veterinary surgical resource. Unlike many medical technologies, the size, reliability, and portability of lasers have improved so rapidly that they are now both economically and practically feasible for the general and specialty veterinarian. Routine laser use in veterinary medicine stands poised to gain large-scale general acceptance for everyday routine and specialty procedures.